2009
DOI: 10.2105/ajph.2008.155473
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cigarette Smoking Initiation in Two Culturally Distinct American Indian Tribes

Abstract: Objectives. To better understand patterns of initiation among American Indians we examined age-related patterns of smoking initiation during adolescence and young adulthood in 2 American Indian tribes. Methods. We used log-rank comparison and a Cox proportional hazard regression model to analyze data from a population-based study of Southwest and Northern Plains American Indians aged 18 to 95 years who initiated smoking by age 18 years or younger. Results. The cumulative incidence of smoking initiation was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
0
27
2
Order By: Relevance
“…These results are inconsistent with previous studies reporting a higher prevalence of smoking in males than females [26][27][28] . In general, nonetheless, self-reported health status in the study sample was consistent with recent research among AI/AN college students 29 …”
Section: Inferential Statisticscontrasting
confidence: 99%
“…These results are inconsistent with previous studies reporting a higher prevalence of smoking in males than females [26][27][28] . In general, nonetheless, self-reported health status in the study sample was consistent with recent research among AI/AN college students 29 …”
Section: Inferential Statisticscontrasting
confidence: 99%
“…Substance abuse patterns have shown great variation, sometimes related to tribe, region, or urban or rural status (4,5,7,8). For example, there are vast differences in alcohol and tobacco use between the Southwest region and the Great Plains (7,9). Further, while high rates of substance use disorders among AI/AN are reported, there is also evidence of high rates of abstinence relative to other groups (1,2).…”
Section: Diversity Within the Ai/an Populationmentioning
confidence: 99%
“…One study of two American Indian tribes, which were culturally and regionally distinct, showed the Northern Plains group had higher cumulative incidence of smoking initiation and earlier ages of initiation than the Southwest group. 26 California Asian Americans are lighter smokers than the general population, with these smokers more likely to be women, not Koreans, higher educated, and bilingual with high English proficiency. 27 One study described how the South Asian community uses cultural tobacco products (eg, paan, paan masala) but have little knowledge about their health harms.…”
Section: Surveillancementioning
confidence: 97%